MENGKAJI PELUANG PROBLEM BASED LEARNING BERORIENTASI ESQ PADA ISU FOOD WASTE DALAM MENINGKATKAN SUISTAINABILY CONSCIOUSNESS SISWA - Apriyoza, Wandra; Fadilah, Muhyiatul (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
The issue of food waste represents a global challenge with profound environmental, economic, and social consequences, serving as a barrier to achieving the Sustainable Development Goals (SDGs). In Indonesia, the high rate of food waste underscores the need for transformative educational strategies that cultivate students’ sustainability consciousness. While numerous studies have explored Problem-Based Learning (PBL) as an effective approach for developing critical thinking, collaboration, and problem-solving skills, limited attention has been given to its potential for internalizing moral and spiritual values that drive sustainable behavior. This article addresses that gap by analyzing the potential of integrating Emotional Spiritual Quotient (ESQ)-oriented PBL to enhance sustainability awareness through the contextual issue of food waste. Using a integrative literature review of 25 key publications (2018–2025) from reputable databases and international reports, the findings reveal that ESQ integration within PBL enriches the affective and conative domains of learning by instilling values of responsibility, balance (mizan), and human stewardship (khalifa fil ardh).The main finding highlights that ESQ-based PBL promotes a holistic form of sustainability consciousness encompassing cognitive, emotional, and spiritual dimensions. Educationally, this model offers an innovative and culturally relevant pedagogical framework for biology learning, empowering students to transform sustainability values into meaningful actions aligned with Indonesia’s moral and religious contexts.